Effect of Rotating Magnetic Field on Microstructure in AlCuSi Alloys - Piotr Mikolajczak (Metals, 2021)
The solidification of AlCuSi alloys with Mn and Fe was studied by rotating a magnetic field to understand the effect of melt flow. The specimens solidified with a forced convection, low cooling rate and low temperature gradient. Electromagnetic stirring generated by an electric coil around the specimens caused a transformation from equiaxed dendritic to rosette morphology, occasionally with spheroids and minor dendrites. The transformation was quantitatively observed with a specific surface Sv, that decreased for almost all alloys and marked the flow effect on α-Al. The computer coupling of phase diagrams and thermochemistry (CALPHAD) technique was applied for the calculation of phase diagrams and property diagrams. Forced convection decreased secondary dendrite arm spacing λ2 in almost all alloys, while it increased slightly in one studied alloy. The length of detrimental β-Al5FeSi phases decreased in the alloy, where β starts to precipitate in the presence of α-Al, while increasing in alloys where β starts as first and grows in the fully liquid melt. The average overall dimension of the Mn-rich phases increased in almost all alloys, and the number density decreased under flow. The modification of spacing for AlSi-eutectics and Al2Cu was analyzed. It was found that the occurrence of Al2Cu does not influence the fluid flow and vice versa.